Dissimilar mispair-recognition spectra of Arabidopsis DNA-mismatch-repair proteins MSH2·MSH6 (MutSα) and MSH2·MSH7 (MutSγ) - Wu, Shiau-Yin (Oxford University Press, 2003)
Besides orthologs of other eukaryotic mismatch-repair (MMR) proteins, plants encode MSH7, a paralog of MSH6. The Arabidopsis thaliana recognition heterodimers AtMSH2·MSH6 (AtMutSα) and AtMSH2·MSH3 (AtMutSβ) were previously found to bind the same subsets of mismatches as their counterparts in other eukaryotes—respectively, base–base mismatches and single extra nucleotides, loopouts of extra nucleotides (one or more) only—but AtMSH2·MSH7 (AtMutSγ) bound well only to a G/T mismatch. To test hypotheses that MSH7 might be specialized for G/T, or for base mismatches in 5-methylcytosine contexts, we compared binding of AtMutSα and AtMutSγ to a series of mismatched DNA oligoduplexes, relative to their (roughly similar) binding to G/T DNA. AtMutSγ bound G/G, G/A, A/A and especially C/A mispairs as well or better than G/T, in contrast to MutSα, for which G/T was clearly the best base mismatch. The presence of 5-methylcytosine adjacent to or in a mispair generally lowered binding by both heterodimers, with no systematic difference between the two. Alignment of protein sequences reveals the absence in MSH7 of the clamp domains that in bacterial MutS proteins—and by inference MSH6 proteins—non-specifically bind the backbone of mismatched DNA, raising new questions as to how clamp domains enhance mismatch recogni tion. Plants must rigorously suppress mutation during mitotic division of meristematic cells that eventually give rise to gametes and may also use MMR proteins to antagonize homeologous recombination. The MSH6 versus MSH7 divergence may reflect specializations for particular mismatches and/or sequence contexts, so as to increase both DNA-replication and meiotic-recombination fidelity, or dedication of MSH6 to the former and MSH7 to the latter, consistent with genetic evidence from wheat.